Angiotensin-converting enzyme activity and inhibition in dogs with cardiac disease and an angiotensin-converting enzyme polymorphism. (October 2017) - Meurs, Kathryn M; Stern, Joshua A; Atkins, Clarke E; Adin, Darcy; Aona, Brent; Condit, Julia; DeFrancesco, Teresa; Reina-Doreste, Yamir; Keene, Bruce W; Tou, Sandy; Ward, Jessica; Woodruff, Kathleen
Objective: The objective of this study was to evaluate angiotensin-converting enzyme (ACE) activity in dogs and with and without an ACE polymorphism in the canine ACE gene, before and after treatment with an ACE inhibitor. Methods: Thirty-one dogs (20 wild-type, 11 ACE polymorphism) with heart disease were evaluated with ACE activity measurement and systolic blood pressure before and after administration of an ACE inhibitor (enalapril). Results: Median pre-treatment ACE activity was significantly lower for ACE polymorphism dogs than for dogs with the wild-type sequence ( P =0.007). After two weeks of an ACE inhibitor, ACE activity was significantly reduced for both genotypes (wild-type, P <0.0001; ACE polymorphism P =0.03); mean post-therapy ACE activity was no different between the groups. Conclusion: An ACE polymorphism is associated with lower levels of ACE activity. Dogs with the polymorphism still experience suppression of ACE activity in response to an ACE inhibitor. It is possible that the genetic status and ACE activity of dogs may impact the response of dogs with this variant to an ACE inhibitor.